Identification of Internal Reference Genes in Peripheral Blood Mononuclear Cells of Cattle Populations Adapted to Hot Arid Normoxia and Cold Arid Hypoxia Environments - Verma, Preeti; Sharma, Ankita; Sodhi, Monika; Tiwari, Manish; Vivek, Prince; Kataria, Ranjit S.; Nirajan, S. K.; Bharti, Vijay K.; Singh, Pawan; Lathwal, S. S.; Sharma, Vishal; Masharing, Nampher; et al. (Frontiers in Genetics, 2022)
To estimate gene expression in a reliable manner, quantitative real-time polymerase chain reaction data require normalisation using a panel of stably expressed reference genes (RGs). To date, information on an appropriate panel of RGs in cattle populations reared at cold arid high-altitude hypoxia and hot arid tropical normoxia environments is not available. Therefore, the present study was carried out to identify a panel of stably expressed RGs from 10 candidate genes (GAPDH, RPL4, EEF1A1, RPS9, HPRT1, UXT, HMBS, B2M, RPS15, and ACTB) in peripheral blood mononuclear cells (PBMCs) of cattle populations reared at cold arid high-altitude hypoxia and hot arid normoxia environments. Four different statistical algorithms: geNorm, NormFinder, BestKeeper, and RefFinder were used to assess the stability of these genes. A total of 30 blood samples were collected: six adult heifers each of Ladakhi (LAC) and Holstein Frisian crosses (HFX) and 4 Jersey (JYC) cows from cold arid high-altitude hypoxia environments (group I) and five adult heifers each of Sahiwal (SAC), Karan Fries (KFC), and Holstein Friesian (HFC) cows from hot arid normoxia environments (group II). Combined analysis of group I and group II resulted in identification of a panel of RGs like RPS9, RPS15, and GAPDH that could act as a useful resource to unravel the accurate transcriptional profile of PBMCs from diverse cattle populations adapted to distinct altitudes.